1984
DOI: 10.1073/pnas.81.4.1053
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mouse metallothionein-I mRNA by bacterial endotoxin is independent of metals and glucocorticoid hormones.

Abstract: Induction of metallothionein-I (MT-I) mRNA by bacterial endotoxin (LPS) was examined. A single injection of LPS induced MT-I mRNA accumulation in both liver and kidney comparable to that induced by heavy metals. Maximal message levels were achieved 6 hr after LPS administration, prior to any increase in either hepatic or renal Zn or Cu. Experiments in which LPS was administered to transgenic mice harboring recombinant genes made by fusing the MT-I gene promoter to the herpes simplex virus thymidine kinase stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
58
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(62 citation statements)
references
References 24 publications
3
58
1
Order By: Relevance
“…MT gene expression is predominantly regulated at the level of transcription [5][6][7][8][9]. Though the mechanism of regulation is poorly understood, rapid induction occurs upon exposure to metals [5] and, in mammalian cells, to various circulating factors such as glucocorticoid hormones [6], ainterferon [7], and interleukin-1 and other mediators of the inflammatory response [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MT gene expression is predominantly regulated at the level of transcription [5][6][7][8][9]. Though the mechanism of regulation is poorly understood, rapid induction occurs upon exposure to metals [5] and, in mammalian cells, to various circulating factors such as glucocorticoid hormones [6], ainterferon [7], and interleukin-1 and other mediators of the inflammatory response [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Though the mechanism of regulation is poorly understood, rapid induction occurs upon exposure to metals [5] and, in mammalian cells, to various circulating factors such as glucocorticoid hormones [6], ainterferon [7], and interleukin-1 and other mediators of the inflammatory response [8,9]. It has been suggested that a common pathway for MT induction involves protein kinase C (PKC) activation since MT levels increase in serum-starved cells after treatment with growth factors and TPA, agents which function in part through PKC activation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Induction of MT synthesis protects macrophages against endotoxin-induced cell killing (I 1). A distinct 5' regulatory site uniquely responsive to endotoxin modulates MT-I gene transcription in mouse liver and kidney (12).…”
mentioning
confidence: 99%
“…The proposed functional roles of metallothioneins include: protection against heavy metal ion intoxication by cadmium or mercury (49); biological response to stress (51,64), and regulation of zinc and copper during development (3,5,52,59). The existence of numerous independent induction responses to different agents regulating MT gene expression suggests a complex role for the regulatory recognition sequences in these genes (16,22,30,43). The sequencing of members of a family of MT genes allowed us both to explore in detail the evolutionary relationship among these genes and to compare the regions of sequence involved in regulating MT gene expression.…”
mentioning
confidence: 99%
“…Metallothioneins are usually isolated as two major isoforms, designated MT-1 and MT-2. The metallothionein (MT) genes are inducible by metal ions (4,17), glucocorticoid hormones (19,20,36,37), stress (51), bacterial endotoxin (16), iodoacetate (18), and interferon (22). Human MT-1 and MT-2 genes show differential expression with metal ion and hormone inducers (57).…”
mentioning
confidence: 99%